8th International Language Learning Conference (8th ILLC 2019) - PPBLT, Pusat Pengajian Bahasa Literasi & Terjemahan (2019)
The 8th ILLC 2019 again serves as a platform for academics, fellow researchers, research scholars and language practitioners of multiple disciplines to convene and share ideas and experiences that capture the development in language learning and teaching around the world. The conference also presents participants with opportunities to build research network and establish contacts for future collaborations, as well as receive in-depth feedback via meaningful discussions.